Od binarności do nowej fali – między modernizmem a postmodernizmem w nowej socjologii dzieciństwa - Małgorzata Kowalik-Olubińska (Problemy Wczesnej Edukacji, 2020)
The area of the author’s investigations is the new study paradigm, known as the new sociology of childhood, formulated at the end of the 20th century. The subject of the author’s interest is one of the currents, known as the new wave, which the author considers in the context of modernism, out of which the current of the new wave has emerged, and postmodernism, which constitutes the significant intellectual background for it. The objective of the article is to depict the way of understanding both the child and childhood contained within the investigative current of the new wave, which has enabled the child to be considered as a fully dimensional and biological, psychological and social being, as well as adaptation of the holistic understanding of childhood as a phenomenon within which culture meets nature, whereas what is social inextricably intertwines with what is natural. The author discusses the modernistic dichotomies, the criticism of which has contributed to the emergence of the new wave of study, within the context of the assumptions of the new sociology of childhood. The author presents conceptual categories which make it possible to get out of dichotomy when describing and analyzing childhood. At the end of the article the author indicates the implications of the assumptions of the new wave analyzed in the article for education of the child.